The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1071/hc19053
|View full text |Cite
|
Sign up to set email alerts
|

Referrals from primary care to community mental health teams: what’s missing?

Abstract: INTRODUCTION:Transfer of care from primary to specialist mental health services almost always requires a referral by hardcopy letter or sent via a structured electronic form. The quality and content of referrals can vary, leading to delays in treatment. AIM:The aim of the research was to explore the quality and content of referral letters received by two urban New Zealand community mental health teams. METHODS:A retrospective audit of 4 months' worth of referrals (n ¼ 92) from primary care to specialist mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A further body of evidence discusses issues likely to affect safety across the care journey (e.g., care team communication problems), though neither embeds relevant patient safety science literature, nor is it conceived of as safety‐relevant research. Such articles instead identify themselves within the spectrum of care quality, 28 or focus on specific issues, such as inadequate care planning, 29 without linking these findings to safety implications. A bibliometric study of research activity on patient safety in community mental health services exemplifies this problem 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further body of evidence discusses issues likely to affect safety across the care journey (e.g., care team communication problems), though neither embeds relevant patient safety science literature, nor is it conceived of as safety‐relevant research. Such articles instead identify themselves within the spectrum of care quality, 28 or focus on specific issues, such as inadequate care planning, 29 without linking these findings to safety implications. A bibliometric study of research activity on patient safety in community mental health services exemplifies this problem 30 .…”
Section: Resultsmentioning
confidence: 99%
“…care team communication problems), though neither embeds relevant patient safety science literature, nor is it conceived of as safety-relevant research. Such articles instead identify themselves within the spectrum of care quality (Allwood, O'Brien, & Glue, 2019), or focus on specific issues, such as inadequate care planning (Newman, O'Reilly, Lee, & Kennedy, 2015), without linking these findings to safety implications. A bibliometric study of research activity on patient safety in community mental health services exemplifies this problem (Silva Souza, Queiroz Bezerra, Santos Pinho, Costa Nunes, & Cardoso Caixeta, 2017).…”
Section: The Developing Evidence Base For Mental Health Patient Safetymentioning
confidence: 99%
“…66 A study in New Zealand suggested that better integrated primary-to-secondary care pathways were needed to improve the quality of referrals and care provision. 67 Another study by Wadoo and colleagues found that improvements in primary health care referrals at a mental health clinic in Qatar resulted in a 93% reduction in referrals with incomplete information, an 80% decrease in referrals that should have been directed elsewhere, and received positive feedback from the primary care physicians. 68 Thus, the referral pathways we have created have the potential to bring about similarly positive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is suggestion that referral guidelines are helpful, they may not be consistently adhered to, though the reasons for this are ambiguous (Hartveit, et al , 2013; Rogers et al , 2013). The content and quality of referrals can also vary which can lead to delayed treatment and impact the efficacy of services (Allwood et al , 2019). A lack of necessary information in the referral may affect whether people reach the most appropriate destination first time and the service’s ability to pre-empt appropriateness for therapy prior to assessment (Dehghan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%